Etika Inovasi dan Kewirausahaan Lembaga Dakwah di Era Disruptif - m gustar umam; Cecep Castrawijaya (GLOBAL SCIENTS PUBLISHER, 2025)
The current disruptive era is characterised by rapid digital technology, artificial intelligence, and platform‐based business models that shake established social and economic structures. In this context, religious propagation institutions face significant challenges: how to remain relevant yet ethical in a dynamic era? This research employs a descriptive qualitative approach through literature review, examining key concepts such as disruptive innovation, organisational resistance, managerial ijtihâd, and Islamic entrepreneurship. The findings indicate that for survival and growth, da’wah institutions must cultivate a culture of managerial ijtihâd, strengthen visionary leadership grounded in Islamic values, and develop an innovation ethics framework that balances the idealism of da’wah mission with contemporary efficiency requirements. The study recommends four main strategic pillars: leadership capacity building, governance reform, digital literacy enhancement, and the formation of innovation ethics committees within da’wah institutions. Accordingly, da’wah organisations are not just able to endure the disruptive era but also become pioneers of dignified socio‐economic change.